2014
DOI: 10.1093/mnras/stu2334
|View full text |Cite
|
Sign up to set email alerts
|

CNO abundances in the globular clusters NGC 1851 and NGC 6752★

Abstract: We measure the C+N+O abundance sum in red giant stars in two Galactic globular clusters, NGC 1851 and NGC 6752. NGC 1851 has a split subgiant branch which could be due to different ages or C+N+O content while NGC 6752 is representative of the least complex globular clusters. For NGC 1851 and NGC 6752, we obtain average values of A(C+N+O) = 8.16 ± 0.10 (σ = 0.34) and 7.62 ± 0.02 (σ = 0.06), respectively. When taking into account the measurement errors, we find a constant C+N+O abundance sum in NGC 6752. The C+N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 100 publications
(113 reference statements)
9
73
3
Order By: Relevance
“…Because of low abundances, most of these elements, excluding CNO sum, have only negligible effect on stellar models (see, e.g., VandenBerg et al 2012). Some GCs, such as NGC 1851 (Yong et al 2015), are reported to contain CNO enhanced stars, but more observations are needed to confirm the ubiquity of these stars in GCs and bulge fields. Jang et al (2014) have shown that some mild CNO enhancement (∆Z CNO ≈ 0.0003), in addition to helium enhancement, would be required to best reproduce the Oosterhoff dichotomy among halo GCs and G1 (G2/G1=0.54) is also well reproduced, if the observed ratio is defined from the peak positions on the histogram showing a period distribution (see Figure 15 of Pietrukowicz et al 2015).…”
Section: 012)mentioning
confidence: 99%
“…Because of low abundances, most of these elements, excluding CNO sum, have only negligible effect on stellar models (see, e.g., VandenBerg et al 2012). Some GCs, such as NGC 1851 (Yong et al 2015), are reported to contain CNO enhanced stars, but more observations are needed to confirm the ubiquity of these stars in GCs and bulge fields. Jang et al (2014) have shown that some mild CNO enhancement (∆Z CNO ≈ 0.0003), in addition to helium enhancement, would be required to best reproduce the Oosterhoff dichotomy among halo GCs and G1 (G2/G1=0.54) is also well reproduced, if the observed ratio is defined from the peak positions on the histogram showing a period distribution (see Figure 15 of Pietrukowicz et al 2015).…”
Section: 012)mentioning
confidence: 99%
“…Amongst its peculiarities is a double sub-giant branch in the colour-magnitude diagram (Milone et al 2008). Other anomalies include a range in C+N+O abundance among the cluster red giants (Yong et al 2009;Ventura et al 2009;Yong, Grundahl & Norris 2015, and references therein), and star-to-star variations in [Fe/H] and s-process elements (Yong & Grundahl 2008;Carretta et al 2010;Gratton et al 2012). The two sub-giant branch populations correlate with the observed abundance variations, as the brighter sub-giant branch is metal-poor and under-abundant in s-process elements compared to the fainter sub-giant population.…”
Section: Introductionmentioning
confidence: 99%
“…Elements whose surface abundance is particularly sensitive to this phenomenon include the light elements Li, Be, B, C (in particular the ratio of C12/C13), and N; C and N are measured by surveys such as APOGEE. There is also evidence, especially in metal-poor stars, for changes in CNO abundances along the giant branch (e.g., Kraft 1994;Yong et al 2015), which requires a mixing process not usually included in standard models whose origin is still uncertain (Angelou et al 2012). However, empirical correlations between stars of known mass and surface abundances can yield powerful insights even without detailed knowledge of the underlying physics.…”
Section: Introductionmentioning
confidence: 99%